Sorption Behavior of Binary Gas CO2/CH4 on Ordered Mesoporous Carbon with the Presence of Water - Wei, Yajuan (2016)
Utilizing dynamic adsorptive method, the static equilibrium sorption data of CO2/CH4 binary gases with four different concentrations on CMK-3 present with water were collected. Compared with similar system only in bulk water, it was found that the whole adsorptive process was considerably complex, which was mixed gas hydrate formation with competitive adsorption. The comprehensive discussions about equilibrium of binary gas on wet CMK-3 have been present here with generating reasonable conclusions. The CO2/CH4 selectivity was also calculated as the important support for CO2/CH4 separation by using gas hydrate formation in porous materials.